Molecular Docking Investigation of Natural Compounds from Inula viscosa and Synthetic Derivatives against Breast Cancer Targets - Noureddine Missoum; Imene Lafri; Amina Ghomri; Houari Bendriss; Mohamed Benbouali; Djamila Kherbouche (International Journal of Computational and Experimental Science and Engineering, 2026)
Novel compounds with significant medicinal properties have attracted considerable interest in therapeutic approaches to treating breast cancer. Different synthetic and natural inhibitors were collected from the literature and docked against (Aromatase, mTOR) receptors. The compounds’ binding affinities were calculated after minimising interactions within the binding pockets of the macromolecular receptors (Aromatase, mTOR). In this work, we use molecular docking methods to identify the ligand that has the best interaction energy with the fourth macromolecule among synthetic and natural products extracted from Inula Viscosa, and also describe binding affinity in order to design new inhibitor ligands. The result shows that ligands (Nepetin, OSI-027) and (3-O-Methylquercetin, Formestane) best inhibited Aromatase and mTOR, respectively. The latter reaches the same conclusion as the study on experimental inhibition.